2017
DOI: 10.5114/hivar.2017.66798
|View full text |Cite
|
Sign up to set email alerts
|

The characteristics of HIV serodiscordant couples consulted at the HIV Out-Patient Clinic in Warsaw

Abstract: Introduction: Human immunodeficiency virus (HIV) is predominantly transmitted through unprotected sexual intercourse. Condom use in long-term relations is uncertain, thus antiretroviral treatment can be the most efficient method of preventing HIV transmission. The objective of this study was to analyze epidemiological characteristics of HIV serodiscordant couples coming to consecutive visits. Material and methods:Data on demographics, HIV viral load, hepatitis B virus (HBV) and hepatitis C virus (HCV) co-infec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Another topic extracted from interviews is the desires, intentions, and fertility experiences of the participants. Previous studies on fertility demands have shown that, like ordinary people, PLWHA have children [6,12,39,[48][49][50][51]; however, the fertility rate has fallen under the influence of various factors [5,52,53]. Most of our study participants also liked to own a child, but fear of the uncertain outcome of illness and orphanage, fear of HIV transmission to the child and wife, the wife's opposition, and inappropriate physical and economic conditions are among the main obstacles to decision making.…”
Section: Discussionmentioning
confidence: 99%
“…Another topic extracted from interviews is the desires, intentions, and fertility experiences of the participants. Previous studies on fertility demands have shown that, like ordinary people, PLWHA have children [6,12,39,[48][49][50][51]; however, the fertility rate has fallen under the influence of various factors [5,52,53]. Most of our study participants also liked to own a child, but fear of the uncertain outcome of illness and orphanage, fear of HIV transmission to the child and wife, the wife's opposition, and inappropriate physical and economic conditions are among the main obstacles to decision making.…”
Section: Discussionmentioning
confidence: 99%